2016
DOI: 10.1177/0033354916679995
|View full text |Cite
|
Sign up to set email alerts
|

Parental Deployment, Adolescent Academic and Social–Behavioral Maladjustment, and Parental Psychological Well-being in Military Families

Abstract: Objective: Increases in the frequency and length of military deployments have raised concerns about the well-being of military families. We examined the relationship between a military parent's deployment and (1) adolescent academic and socialbehavioral maladjustment and (2) parental psychological well-being. Methods: We collected data from April 2013 through January 2014 from 1021 families of enlisted US Army personnel with children aged 12 or 13 during the Military Teenagers' Environments, Exercise, and Nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
(52 reference statements)
1
14
0
Order By: Relevance
“…Consistent with the literature (Aranda et al, 2011; Barnes, Davis, & Treiber, 2007; Chandra, Lara-Cinisomo et al, 2010; Chandra, Martin et al, 2010; Chartrand et al, 2008; Flake et al, 2009; Huebner et al, 2007; Lester et al, 2010; Nicosia et al, 2017), this study found that deployment to a combat zone impacted the health and behavior of the SMV’s children, though a decline in each of the five health and behavior domains was only reported for a minority of the sample. A very small minority of the caregivers reported improvement in their children’s health and behavior.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with the literature (Aranda et al, 2011; Barnes, Davis, & Treiber, 2007; Chandra, Lara-Cinisomo et al, 2010; Chandra, Martin et al, 2010; Chartrand et al, 2008; Flake et al, 2009; Huebner et al, 2007; Lester et al, 2010; Nicosia et al, 2017), this study found that deployment to a combat zone impacted the health and behavior of the SMV’s children, though a decline in each of the five health and behavior domains was only reported for a minority of the sample. A very small minority of the caregivers reported improvement in their children’s health and behavior.…”
Section: Discussionsupporting
confidence: 88%
“…For some families, deployment and reintegration can be a period for growth, adaptability, and resilience (Chandra, Martin, Hawkins, & Richardson, 2010; Cozza, Chun, & Polo, 2005; Wadsworth et al, 2016), but for others, it can be a source of significant stress (Cozza et al, 2005; Flake, Davis, Johnson, & Middleton, 2009; Gibbs, Martin, Kupper, & Johnson, 2007; Lester et al, 2010). The negative impact of parental deployment during the post-9/11 combat period on emotional, behavioral, physical, and educational outcomes among children in military families is well documented (Aranda, Middleton, Flake, & Davis, 2011; Chandra, Burns, Tanielian, & Jaycox, 2011; Chandra, Martin et al, 2010; Chartrand, Frank, White, & Shope, 2008; Flake et al, 2009; Huebner, Mancini, Wilcox, Grass, & Grass, 2007; Lester et al, 2010; Nicosia, Wong, Shier, Massachi, & Datar, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The relation between high caregiving burden and parenting one or more child under 18 years is of particular concern for many military families long-term. The impact of post-9/11 combat deployments, TBI, combat injuries, and caregiving on children and families is well documented (Brickell, French, Lippa, & Lange, 2017; Chandra, Burns, Tanielian, & Jaycox, 2011; Flake, Davis, Johnson, & Middleton, 2009; Huebner, Mancini, Wilcox, Grass, & Grass, 2007; Lester et al, 2010; Nicosia, Wong, Shier, Massachi, & Datar, 2017; Wadsworth et al, 2016). Because of the demands of caring for the SMV, the children often receive less time and attention from the caregiver and many also take on caregiving duties resulting in no personal time for themselves (Ramchand et al, 2014; Saban, Hogan, Hogan, & Pape, 2015; Tanielian, Ramchand, Fisher, Sims, & Harris, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, familial relationships are an identified concern reported from military personnel; 44% of post-9/11 veterans worried that deployment affected their relationship with their children (Pew Research Center, 2011). Such relationship concerns are not necessarily the academic and behavioral concerns psychology, psychiatry, and counseling researchers have explored (Nicosia et al, 2017). Within counseling research, there is a need to incorporate perspectives of military parents and children, rather than relying on school counselors as participants.…”
Section: Prosek and Burginmentioning
confidence: 99%